2010
DOI: 10.1002/pmic.200900685
|View full text |Cite|
|
Sign up to set email alerts
|

Mitochondrial comparative proteomics of human ovarian cancer cells and their platinum‐resistant sublines

Abstract: Resistance to platinum-based chemotherapy is the major obstacle to successful treatment of ovarian cancer. It is evident that mitochondrial defects and the dysfunctions of oxidative phosphorylation and energy production in ovarian cancer cells were directly related to their resistance to platinum drugs. Using 2-D DIGE, we compared mitochondrial proteins from two platinum-sensitive human ovarian cancer cell lines (SKOV3 and A2780) with that of four platinum-resistant sublines (SKOV3/CDDP, SKOV3/CBP, A2780/CDDP,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 50 publications
0
32
0
Order By: Relevance
“…Furthermore, short hairpin RNA (shRNA)-mediated loss in functional PRDX3 expression led to significant suppression of migration and transendothelial invasion in MCF-7 breast cancer cells in vitro and significant inhibition of breast cancer metastasis in vivo (Kim et al, 2009;Li et al, 2009;Liu et al, 2010;Wu et al, 2010). Recently, abundant evidence has also confirmed that tissue-specific expression of PRDX3 plays an important role in hepatocarcinoma progression (Dai et al, 2010). Qiao et al has analyzed the comparative proteomic profiles between HCC tumors and adjacent non-tumor tissues by 2-DE and MALDI-TOF MS, and identified differentially expressed molecules which may help to develop effective therapeutic strategies against HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, short hairpin RNA (shRNA)-mediated loss in functional PRDX3 expression led to significant suppression of migration and transendothelial invasion in MCF-7 breast cancer cells in vitro and significant inhibition of breast cancer metastasis in vivo (Kim et al, 2009;Li et al, 2009;Liu et al, 2010;Wu et al, 2010). Recently, abundant evidence has also confirmed that tissue-specific expression of PRDX3 plays an important role in hepatocarcinoma progression (Dai et al, 2010). Qiao et al has analyzed the comparative proteomic profiles between HCC tumors and adjacent non-tumor tissues by 2-DE and MALDI-TOF MS, and identified differentially expressed molecules which may help to develop effective therapeutic strategies against HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Classical antioxidant genes related to cancer are the superoxide dismutase (SOD), catalase, GST, glutathione peroxidase, peroxiredoxins and thioredoxin (Trx) (12)(13)(14)(15) (19). PRDX3 has been shown to be overexpressed in mesothelioma, hepatocellular carcinoma, breast cancer and ovarian cancer (20)(21)(22)(23), which suggest that PRDX3 may be involved in tumorigenesis and progression.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have demonstrated that resistance to platinum drugs in ovarian cancer cells is linked to mitochondrial dysfunctions in oxidative phosphorylation and energy production (36 -40). Mitochondrial proteomic analysis of drug-resistant cells has shown that five mitochondrial proteins (ATP-a, PRDX3, PHB, ETF, and ALDH) that participate in the electron transport respiratory chain are down-regulated in drug-resistant cell lines (41). PRDX3 is involved in redox regulation of the cell to protect radical-sensitive enzymes from oxidative damage.…”
mentioning
confidence: 99%